STRENGTHENING NATIONAL FOOD SECURITY IN UZBEKISTAN (Ustozlar uchun, 2025)
Food security remains a critical global challenge, with implications for economic stability, social well-being, and sustainable development. This study analyzes Uzbekistan’s experience in strengthening food security, examining trends in agricultural production, per capita availability, and food processing capacity. The findings reveal substantial growth in crop and livestock output, contributing to improved domestic food supply and nutritional outcomes. It also provides insights not only for Uzbekistan but also for other developing countries seeking to ensure sustainable and equitable food security under conditions of globalization and climate variability.